Sociolinguistic Variation in Learners’ Classroom Discourse - Syahdan Syahdan; Lalu Muhaimi; M. Fadjri; Untung Waluyo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2019)
Abstract : This study investigates the use of the sociolinguistic variation in classroom discourse by learners of English as a foreign language. By using qualitative descriptive method, this study finds out that (a) sociolinguistic variation tends to be used more in informal speech than in formal settings; (b) higher English proficiency and frequent interaction with peers in the classroom and with native speakers of English promote the appropriate contextual usage of sociolinguistic variation; and (c) females tend to adopt more formal language style than males. This study also finds that learners’ patterns of sociolinguistic variation closely follow those of their teachers and textbooks, suggesting the necessity of explicit instruction in sociolinguistic variants in classrooms.Keywords : sociolinguistics; sociolinguistic variation; inter-language; language acquisition.